The Procedure of Seed Potato Certification in Morocco (Atlas Journal of Biology, 2017)
The potato -Solanum tuberosum- is a geophyte of the Solanaceae family and represents the first crops in Morocco. Thanks to its high nutritional value, the seed requirements attain around 160000 T of which 70% originate from the previous production, the reason behind the limitation of the market’s development. Considering the importance of the certified seeds, Morocco has signed a program contract to develop this sector. The production of certified potato seedling is a whole process that begins with the selection of plants and goes on until the marketing of the product where the producer should absolutely respect the cultivation processes and hygiene standards. Establishing and ensuring compliance with these standards is carried out by the National Office of Sanitary Safety and Food Supplies (ONSSA). The purpose of the present work is to summarize and represent briefly the certification standards of potato seeds in Morocco.